Dietary Stevia Residue Extract Supplementation Improves Antioxidant Capacity and Intestinal Microbial Composition of Weaned Piglets - Shuai Liu; Yunxia Xiong; Shuting Cao; Xiaolu Wen; Hao Xiao; Yajing Li; Lei Chi; Dongsheng He; Zongyong Jiang; Li Wang (MDPI AG, 2022)
This study aimed to investigate the effects of diet supplementation with stevia residue extract (SRE) on growth performance, intestinal health, and antioxidant capacity of weaned piglets. A total of 144 weaned piglets (body weight 6.8 ± 0.5 kg) were randomly selected and allocated into four treatment groups with six replicates of six pigs/pen. The treatments consisted of a basal diet without SRE or basal diet supplemented with 100, 200, or 400 mg/kg SRE. The results showed that the addition of 200 mg/kg SRE to the diet significantly reduced (p < 0.05) the diarrhea rate of piglets compared with the control group. The supplementation of 400 mg/kg SRE in the diet significantly reduced the piglets' serum MDA content and significantly increased (p < 0.05) the T-AOC, T-SOD, and GSH-PX activity in the serum. The dietary supplementation with 400 mg/kg SRE significantly increased (p < 0.05) the CAT and GSH-PX activity in the liver. Moreover, the supplementation of 400 mg/kg SRE in the diet significantly increased (p < 0.05) the relative abundance of Prevotellaceae (genus) and Roseburia (genus) beneficial bacteria compared to the control group. Spearman's correlation analysis showed that Prevotella (genus) abundance was positively correlated with liver GSH-PX activity and acetic acid content of colon contents. In conclusion, the supplementation of 400 mg/kg SRE to the diet can improve piglet health by regulating antioxidant reduction homeostasis, which may also be associated with an increase in the relative numbers of potentially beneficial bacteria.